What Does It Mean To Be a Badly Behaved Animal? An Answer from the Devadatta Stories of the Pāli Jātakas - Appleton, Naomi (Religions, 2019)
The many animals that appear in the Pāli Jātakatthavaṇṇanā often mirror human predicaments, society and language, and this has prompted largely allegorical readings of the stories. In addition, in many cases the animals are identified as past lives of important human characters, potentially diminishing their animality further. In particular, the Buddha's repeated rebirth as a range of virtuous and wise animals tells us plenty about the Buddha, but arguably little about animals. Nonetheless, in this article I argue that the jātakas are able to tell us interesting things about the capabilities of animals. By using stories of another key animal character-namely Devadatta, the Buddha's nemesis-I explore what might be distinctive about the ability of animals to misbehave. Since Devadatta appears 28 times as an animal and 46 as a human, he allows us to probe whether or not the text's compilers saw a difference between human and animal capacities for evil. In the process, I raise questions about how we should view animal tales in the Jātakas more broadly, and highlight the productive tension between animals as unfortunate fellow travellers in the cycle of rebirth, and animals as literary devices that shed light on human behaviour.